2018
DOI: 10.1080/13607863.2018.1452898
|View full text |Cite
|
Sign up to set email alerts
|

Views and experiences of care home staff on managing behaviours that challenge in dementia: a national survey in England

Abstract: BtC are commonly and frequently experienced by care staff, who consider individual approaches, having time and good communication are key to successful management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In addition, the caregivers were influenced by singing (CS), as they described themselves as more relaxed and happy and less anxious of having to deal with possible aggression from the persons they cared for (Hammar et al, 2011c). Multiple studies focusing on different kinds of music interventions suggested that interventions should be person-centered (McCormack, 2004), which means that the music that is played or sung should be based on the person’s preference, and preferably from his or her youth, as persons with dementia tend to remember that kind of music (Spiro, 2010). Studies focusing on CS have included both persons with Alzheimer’s disease and persons with vascular dementia, but no studies have focused on possible differences regarding these diagnoses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the caregivers were influenced by singing (CS), as they described themselves as more relaxed and happy and less anxious of having to deal with possible aggression from the persons they cared for (Hammar et al, 2011c). Multiple studies focusing on different kinds of music interventions suggested that interventions should be person-centered (McCormack, 2004), which means that the music that is played or sung should be based on the person’s preference, and preferably from his or her youth, as persons with dementia tend to remember that kind of music (Spiro, 2010). Studies focusing on CS have included both persons with Alzheimer’s disease and persons with vascular dementia, but no studies have focused on possible differences regarding these diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of diagnosis, dementia is associated with cognitive impairments, and responsive behaviors such as such as aggression, resistant behaviors (commonly to care), wandering, and screaming. (Aarsland, 2020;Mallon et al, 2019). Persons with dementia commonly express responsive behaviors in interaction with each other, such as in care situations when personal integrity is perceived as threatened (Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%